AN APPLICATION OF RESEARCH AND DEVELOPMENT METHODS IN MANAGEMENT OF DIGITAL MEDIA TO IMPROVE THE LEARNING MINDSET STUDENTS - Heni Wulandari; Suherman Suherman; Sri Wahyuni; Nabila Octabia Cahyandi (SEAN Institute, 2023)
This study aims to develop and produce digital media-based teaching materials in English lessons that are validated and describe their validity, practicality and effectiveness. This study applied the Research and Development method with five stages (ADDIE), namely Analysis, Design, Development, Implementation and Evaluation. The development model used is the Luther-Sutopo version of the multimedia development model which consists of six stages, namely drafting, designing, gathering material, manufacturing, testing and distribution. Digital media-based teaching materials are expected to present interesting and interactive English learning materials, so that it will be easier for teachers to carry out learning and can improve student achievement in the field of education.